2011
DOI: 10.1097/aap.0b013e3182330b95
|View full text |Cite
|
Sign up to set email alerts
|

Is Pulmonary Function Affected by Bilateral Dual Transversus Abdominis Plane Block? A Randomized, Placebo-Controlled, Double-Blind, Crossover Pilot Study in Healthy Male Volunteers

Abstract: The administration of ultrasound-guided bilateral dual TAP blocks does not result in clinically relevant or statistically significant changes in the pulmonary function in healthy male subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…[17,18] This is consistent with the results of our study. Zones 1 and 4 are located at levels T6 to T8, zone 7 is located at level L1.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[17,18] This is consistent with the results of our study. Zones 1 and 4 are located at levels T6 to T8, zone 7 is located at level L1.…”
Section: Discussionsupporting
confidence: 93%
“…Most of the previous studies [7,17,18] only reported and analyzed the comparison of different plane levels, but never analyzed the diffusion of the block from midline to the back. If we use TAP block for postoperative analgesia purpose without knowing the diffusion pattern, for example, using TAP block on an upper lateral abdominal incision, it likely to cause poor analgesia results.…”
Section: Discussionmentioning
confidence: 99%
“…Niraj et al studied the analgesic effect of subcostal transversus abdominis plane catheters versus epidural catheters, and in that study 45% of TAP catheters had to be re-sited within the first 24 hours after surgery [13]. In a study of pulmonary function in healthy volunteers that had bilateral TAP blockade, 2 out of 11 volunteers had bilateral block failure [14]. We should have anticipated problems with block failure and catheter displacements and taken this into account in our sample size calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Preincisional timing for injection has yet to be tested in randomized trials. 298,299,302,303,[306][307][308][309] Reported complications include intraperitoneal injection or hemorrhage, transient femoral nerve palsy, and local anesthetic toxicity. [310][311][312] In summary,…”
Section: Transversus Abdominis Plane Blockmentioning
confidence: 99%